Improving the Electrocatalytic Activities and CO Tolerance of Pt NPs by Incorporating TiO2 Nanocubes onto Carbon Supports. Issue 8 (18th February 2021) - Antoniassi, Rodolfo M.; Quiroz, Jhon; Barbosa, Eduardo C. M.; Parreira, Luanna S.; Isidoro, Roberta A.; Spinacé, Estevam V.; Silva, Julio C. M.; Camargo, Pedro. H. C.
Abstract: Designing efficient anode CO‐tolerant electrocatalysts is critical in low‐temperature fuel cell catalysts fueled either by H2 /CO or alcohol. We demonstrate that the incorporation of TiO2 nanocubes (TiO2 NCs) on Carbon Vulcan supports, followed by the synthesis of Pt NPs at their surface (Pt/TiO2 NCs‐C material), led to improvements in performance towards the electrooxidation of carbon monoxide, ethanol, methanol, ethylene glycol, and glycerol in acidic media relative to the commercial Pt/C and Pt/TiO2 ‐C counterparts employing commercial TiO2 . The nanocubes enabled changes in the electronic properties of Pt NPs while contributing to the bifunctional mechanism as compared to Pt/C and Pt/TiO2 ‐C with commercial TiO2 . Fuel cell experiments fed with H2 /CO steam showed that Pt/TiO2 NCs‐C employing nanocubes was resistant to CO‐poisoning, yielding superior performance in operational conditions. The results reported herein have important implications for developing electrocatalysts with superior performances in PEMFCs. Abstract : Improved electrocatalysis : The incorporation of TiO2 nanocubes (TiO2 NCs) on Carbon Vulcan supports, followed by the synthesis of Pt NPs at their surface (Pt/TiO2 NCs‐C material), led to improvements in performance towards the electrooxidation of carbon monoxide, ethanol, methanol, ethylene glycol, and glycerol in acidic media relative to the commercial Pt/C and Pt/TiO2 ‐C counterparts employing commercial TiO2 .